Hypouricaemic action of mangiferin results from metabolite norathyriol via inhibiting xanthine oxidase activity. (1st September 2016) - Niu, Yanfen; Liu, Jia; Liu, Hai-Yang; Gao, Li-Hui; Feng, Guo-Hua; Liu, Xu; Li, Ling
Abstract: Context Mangiferin has been reported to possess a potential hypouricaemic effect. However, the pharmacokinetic studies in rats showed that its oral bioavailability was only 1.2%, suggesting that mangiferin metabolites might exert the action. Objective The hypouricaemic effect and the xanthine oxidase inhibition of mangiferin and norathyriol, a mangiferin metabolite, were investigated. Inhibition of norathyriol analogues (compounds3 –9 ) toward xanthine oxidase was also evaluated. Materials and methods For a dose-dependent study, mangiferin (1.5–6.0 mg/kg) and norathyriol (0.92–3.7 mg/kg) were administered intragastrically to mice twice daily for five times. For a time-course study, mice received mangiferin and norathyriol both at a single dose of 7.1 μmol/kg. In vitro, inhibition of test compounds (2.4–2.4 mM) against xanthine oxidase activity was evaluated by the spectrophotometrical method. The inhibition type was identified from Lineweaver–Burk plots. Results Norathyriol (0.92, 1.85 and 3.7 mg/kg) dose dependently decreased the serum urate levels by 27.0, 33.6 and 37.4%, respectively. The action was more potent than that of mangiferin at the low dose, but was equivalent at the higher doses. Additionally, the hypouricaemic action of them exhibited a time dependence. In vitro, norathyriol markedly inhibited the xanthine oxidase activities, with the IC50 value of 44.6 μM, but mangiferin did not. The kinetic studies showed that norathyriol was an uncompetitive inhibitor by Lineweaver–Burk plots. The structure–activity relationships exhibited that three hydroxyl groups in norathyriol at the C-1, C-3 and C-6 positions were essential for maintaining xanthine oxidase inhibition. Discussion and conclusion Norathyriol was responsible for the hypouricaemic effect of mangiferin via inhibiting xanthine oxidase activity.